The Effect of Service Quality, Price and Product Quality on Customer Satisfaction at PT. Bukit Asam Tbk - Salman, Salman; Rahayu, Sri; Maftuhah, Nurrahmi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
This study aims to determine the effect of service quality, price, and product quality on customer satisfaction at PT Bukit Asam Tbk. The object of this study is customers of PT Bukit Asam Tbk. The sampling technique used a purposive sampling method with 30 customers. The research method used is associative research, utilizing the type of primary data obtained from the results of questionnaire answers. The analysis technique used is multiple linear regression. The results of this study indicate that simultaneously, there is a positive and significant influence of service quality, price, and product quality on PT Bukit Asam Tbk customer satisfaction. Partial testing shows a positive and significant effect of service quality on customer satisfaction of PT Bukit Asam Tbk. Partially, there is a positive and significant effect of price on customer satisfaction of PT Bukit Asam Tbk. Partially, there is a positive and significant effect of product quality on customer satisfaction of PT Bukit Asam Tbk.